PENGELOLAAN DAN PELESTARIAN LINGKUNGAN BERBASIS KOMUNITAS (Studi Kasus Desa Wisata Sidoakur, Jethak II, Sidokarto, Godean, Sleman, Daerah Istimewa Yogyakarta) - , CITRA DYAH PUSPARINI; , Destha Titi Raharjana, S.Sos, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
It is certain that every activity human does in a certain community has effect toward to environment. There is always such a interaction between human and their environment. As a matter of fact, tourism exactly has its close interaction with the environment. Based on promoting the tourism objects in a certain area, as a result tourism tends to create such environment damages, due to the tourists who visit those areas. It is hoped that environment conservation could be arouse and implemented through the awareness of the human themselves according to the ecotourism principalities in order to conserve the environment that would be free from any kinds of pollution. This study was conducted in Sidoakur Tourism Village Jethak II Sidoakarto Godean Sleman DIY, a tourism village which has environment and culture bases policy. The aims of this strudy followed : (1) to find out certain nfactors that have been done by the villagers of Sidoakur Tourism Village Jethak II Sidokarto Godean Sleman DIY in doing some efforts to conserve their environment, (2) to find out such strategies in environment conservation which have been implemented there, and (3) to find out the benefits that could be taken as a result from the environments conservation strategies. The descriptive study was used to describe and analyze the phenomenon and the situation in the object of study and also o provide the facts based on the theoretical framework in order to get clearer comprehension in making the conclusion.